Pemanfaatan Aplikasi Media Sosial Instagram terhadap Pengembangan Media Dakwah di Masjid Al-Ikhlash Perumahan Cimareme Indah - Kharisma Fadhlur Rahman; M. Wildan Yahya; Parihat Kamil (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. The use of social media in preaching has become an increasingly important phenomenon in the context of religious communication. This study aims to analyze the use of the Instagram social media application for the development of da'wah media through the mosque's Instagram account @alikhlash.cimareme. The research was conducted using a qualitative and descriptive approach, involving data collection from observation, interviews, and analysis of social media content. The results of the study show that the management of the Al-Ikhlash Mosque uses social media as an effective means of da'wah. They spread inspirational religious messages and provide valuable information to the public through interesting content such as Al-Quran quotes, hadiths, short video lectures, infographics on religious knowledge, and inspirational stories. The strategy of collaboration with well-known scholars also brings great benefits, with the contribution of the scholars giving credibility to the religious messages being disseminated, attracting the attention of more congregations, and increasing the authority of content. In addition, this study also identified variations in the congregation's response to content on the Instagram social media account of the Masjid @alikhlash.cimareme, including positive responses, welcoming responses, neutral responses, critical responses, and participatory responses. Nonetheless, obstacles in the use of social media were also identified, especially in terms of account management that is centered on one individual. This research identified a wide range of opportunities in the use of social media, including wider reach, creative and interactive content, collaboration with communities and influencers, as well as the use of hashtags, feedback, and direct interaction. This research contributes to understanding the effectiveness of using social media in the context of preaching in mosques, with practical implications in designing more effective and creative da'wah strategies in the digital era. The conclusions and recommendations from this research can help mosque administrators, da'wah practitioners, and the Muslim community to better understand and utilize social media in spreading religious messages effectively. Abstrak. Pemanfaatan media sosial dalam dakwah telah menjadi fenomena yang semakin penting dalam konteks komunikasi agama. Penelitian ini bertujuan untuk menganalisis pemanfaatan aplikasi media sosial Instagram terhadap pengembangan media dakwah melalui akun Instagram masjid @alikhlash.cimareme. Penelitian dilakukan dengan pendekatan kualitatif dan desktiptif, melibatkan pengumpulan data dari observasi, wawancara, dan analisis konten media sosial. Hasil penelitian menunjukkan bahwa Pengurus Masjid Al-Ikhlash menggunakan media sosial sebagai sarana dakwah yang efektif. Mereka menyebarkan pesan-pesan agama yang inspiratif dan memberikan informasi berharga kepada masyarakat melalui konten-konten menarik seperti kutipan Al-Quran, hadist, video ceramah singkat, infografis pengetahuan agama, dan kisah-kisah inspiratif. Strategi kolaborasi dengan ulama terkenal juga membawa manfaat besar, dengan kontribusi ulama memberikan kredibilitas pada pesan-pesan agama yang disebarkan, menarik perhatian lebih banyak jemaah, dan meningkatkan otoritas konten. Selain itu, penelitian ini juga mengidentifikasi variasi respon jemaah terhadap konten yang ada pada akun media sosial Instagram Masjid @alikhlash.cimareme, termasuk respon positif, respon menyambut baik, respon netral, respon kritis, dan respon partisipatif. Meskipun demikian, hambatan dalam pemanfaatan media sosial juga teridentifikasi, terutama dalam hal manajemen akun yang terpusat pada satu individu. Penelitian ini mengidentifikasi peluang yang luas dalam pemanfaatan media sosial, termasuk jangkauan yang lebih luas, konten yang kreatif dan interaktif, kolaborasi dengan komunitas dan influencer, serta penggunaan hastag, feedback, dan interaksi langsung. Penelitian ini memberikan kontribusi dalam memahami efektivitas penggunaan media sosial dalam konteks dakwah di Masjid, dengan implikasi praktis dalam merancang strategi dakwah yang lebih efektif dan kreatif di era digital. Kesimpulan dan rekomendasi dari penelitian ini dapat membantu pengurus masjid, praktisi dakwah, serta komunitas Muslim untuk lebih memahami dan memanfaatkan media sosial dalam menyebarkan pesan-pesan agama secara efektif.